Action Research and Teacher Thinking: The First Phase of the Action Research on Action Research Project at the University of Wisconsin Madison - Noffke, Susan E.; Zeichner, Kenneth M. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
This report on action research projects conducted by student teachers as a part of their preservice teacher preparation program focuses on how action research improves the understanding of educational practices by the practitioner-researchers themselves. Two major topics are discussed. First, specific types of claims about the impact of action research on teachers' understandings are identified from selected projects conducted in the United States, the United Kingdom, and Australia. A description of the methodologies used to collect supporting data is included. The second major topic of the paper is a description of the "Action Research on Action Research" project now underway at the University of Wisconsin, Madison. Action research has been used in the University's elementary student teaching program for several years as one way to provide opportunities for growth in the ability to reflect systematically on one's own teaching practice. A comprehensive review of the literature on the impact action research can have on teacher thinking introduces the main body of the paper. (JD)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (Washington, DC, April 20-24, 1987).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Action Research; Higher Education; Preservice Teacher Education; Program Development; Program Effectiveness; Research Utilization; Self Evaluation (Individuals); Student Teachers; Teacher Attitudes; Teacher Education Programs; Teacher Researchers; Speeches/Meeting Papers; Reports, Descriptive